XmnI polymorphism is associated with fetal hemoglobin levels in hypoplastic syndromes - Shimmoto, Marily Maria Azevedo; Vicari, Perla; Fernandes, Andréa Cristina; Guimarães, Gustavo Stuani; Figueiredo, Maria Stella (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Acquired fetal hemo- globin (HbF) elevation has been implicated as a prognostic factor in dyserythropoietic disorders. Our objectives were to examine acquired HbF in- creases in aplastic anemia (AA) and paroxysmal nocturnal hemoglobinuria (PNH) patients, and to evaluate whether there is an association between the presence of XmnI and 5’ hypersensitive site locus control region (LCR-HS2) polymorphisms and the HbF levels. DESIGN AND SETTING: Cross-sectional study at the Hematology and Blood Transfusion Service of Universidade Federal de São Paulo — Escola Paulista de Medicina. METHODS: We studied a group of 37 patients with AA and/or PNH. Polymerase chain reaction (PCR) and enzymatic digestion were utilized to analyze XmnI polymorphisms; and PCR, cloning and automated sequencing for the HS2 polymorphisms. RESULTS: The mean HbF level was 2.32%, but there was no significant difference in HbF level between the AA and PNH groups (p = 0.46). HbF levels of less than 1.0% showed a significant correlation with absence of the XmnI (+) polymor- phism (p = 0.02). The presence of the XmnI allele was greater in the AA group (p = 0.007). CONCLUSIONS: XmnI polymorphism absence reduction is associated with acquired HbF eleva- tion. Further studies are required to confirm these observations and make treatment, prognosis and survival comparisons.